2007
DOI: 10.1080/10942910601098031
|View full text |Cite
|
Sign up to set email alerts
|

Sensory and Microbiological Quality of a Baked Product Containing Xylitol as an Alternative Sweetener

Abstract: The potential application of xylitol, as low energy alternative sweetener, was investigated in baked products. Xylitol was used as sole sweetener in home made cookies, the properties of which were compared to products containing sucrose and glucose. The sensory properties were evaluated by discrimination, descriptive, and affective tests. The storage time of one and two weeks, both at 4-6°C and at 20-22°C did not show significant impact on the flavor and texture properties of all cookies. After being stored fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
22
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(32 citation statements)
references
References 18 publications
5
22
0
1
Order By: Relevance
“…Xylitol is more hygroscopic than sucrose (Winkelhausen et al . ); therefore, it seems reasonable that partial or complete elimination of sucrose led to a reduction in the water activity of dietetic cakes. As suggested by Winkelhausen et al .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Xylitol is more hygroscopic than sucrose (Winkelhausen et al . ); therefore, it seems reasonable that partial or complete elimination of sucrose led to a reduction in the water activity of dietetic cakes. As suggested by Winkelhausen et al .…”
Section: Resultsmentioning
confidence: 99%
“…In a comparative study about the effect of xylitol and sucrose on shelf‐life of sponge cakes, samples produced with sucrose showed mold spoilage after 15 days of storage, while no mold spoilage was observed in samples containing 5% xylitol up to 29 days (Winkelhausen et al . ).…”
Section: Introductionmentioning
confidence: 97%
“…Granström et al (2007) reported on the use of xylitol as a raw material for production of L-lyxose, L-xylose and Larabinose. Additionally, xylitol can be used for extending the shelf life of foods (Parajó et al 1998;Winkelhausen et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Xylitol can provide about 10 kJ/g energy, which is 40% less energy than sucrose (Winkelhausen et al . ). Winkelhausen et al .…”
Section: Introductionmentioning
confidence: 97%